The Emerging Roles for Telomerase in the Central Nervous System - Liu, Meng-Ying; Nemes, Ashley; Zhou, Qi-Gang (Frontiers in Molecular Neuroscience, 2018)
Telomerase, a specialized ribonucleoprotein enzyme complex, maintains telomere length at the 3' end of chromosomes, and functions importantly in stem cells, cancer and aging. Telomerase exists in neural stem cells (NSCs) and neural progenitor cells (NPCs), at a high level in the developing and adult brains of humans and rodents. Increasing studies have demonstrated that telomerase in NSCs/NPCs plays important roles in cell proliferation, neuronal differentiation, neuronal survival, and neuritogenesis. In addition, recent works have shown that telomerase reverse transcriptase (TERT) can protect newborn neurons from apoptosis and excitotoxicity. However, to date, the link between telomerase and diseases in the central nervous system (CNS) is not well reviewed. Here we analyze the evidence and summarize the important roles of telomerase in the CNS. Understanding the roles of telomerase in the nervous system is not only important to gain further insight into the process of the neural cell life cycle, but would also provide novel therapeutic applications in CNS diseases such as neurodegenerative condiction, mood disorders, aging, and other ailments.